PENGARUH INDUKSI GIBERELIN TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI MERAH (Capsicum annum L) SEBAGAI SUMBER BELAJAR BIOLOGI - Yeni, Titin; Mulyani, HRA (Bioedukasi Jurnal Pendidikan Biologi, 2014)
The research was conducted on February 2, 2012 until April 30, 2012 at the Green House in University of Muhammadiyah Metro. The purposes of this study are (1) to determine the effect of induction of gibberellin on the growth and production of red pepper plants (Capsicum annum L). (2) To determine the induction of 200 ppm gibberellin can provide growth and production of red pepper (Capsicum annum L) is best. This study used statistical design of experiments using the Rancangan Acak Lengkap (RAL) and the data analysis by using the path on ANAVA toward the production chilies with 3 treatments and 1 control. Each trial has treatments, as follow: without gibberellin induction as a control (H0), 150 ppm gibberellin induction (H1), induction of gibberellin is 200 ppm (H2), and induction of gibberellin is 250 ppm (H3). The population in this study is overall  of the 3 treatments and 1 control with 4 replications, and the total is 16 red pepper plant. The sample in this study is the whole of plants, the total is 12 samples of red pepper plant. Based on the research results can be concluded that;  (1) There is an induction effect of gibberellin on the growth and production of red pepper plants (2) Induction of gibberellin is 200 ppm delivers growth and crop production the best chili. For education research results can be used as a learning resource material of growth and developmental biology.  Kata Kunci:  induksi giberelin, pertumbuhan cabai merah, produksi cabai merah, sumber belajar biologi.